2004
DOI: 10.1007/s00464-003-8926-y
|View full text |Cite
|
Sign up to set email alerts
|

Experience with over 3,000 open and laparoscopic bariatric procedures: Multivariate analysis of factors related to leak and resultant mortality

Abstract: The data suggests that older, heavier male patients with multiple comorbid conditions are at increased risk for leak and mortality. Surgeons early in their learning curve should avoid these high-risk patients to reduce complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
161
2
7

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(176 citation statements)
references
References 17 publications
6
161
2
7
Order By: Relevance
“…Increased risk factors for early mortality include: revisional surgery, biliopancreatic diversion Ͼ gastric bypass (GBP) Ͼ laparoscopic adjustable gastric banding, high BMI (usually Ͼ 50 kg/m 2 ), and male gender (5-7). Data linking type 2 diabetes, OSA, and HTN to risk of early mortality are less consistent (6,8).…”
Section: Multidisciplinary Care: Operative Riskmentioning
confidence: 98%
See 1 more Smart Citation
“…Increased risk factors for early mortality include: revisional surgery, biliopancreatic diversion Ͼ gastric bypass (GBP) Ͼ laparoscopic adjustable gastric banding, high BMI (usually Ͼ 50 kg/m 2 ), and male gender (5-7). Data linking type 2 diabetes, OSA, and HTN to risk of early mortality are less consistent (6,8).…”
Section: Multidisciplinary Care: Operative Riskmentioning
confidence: 98%
“…Approximately two-thirds of early postoperative mortality from WLS is associated with anastomotic leaks and PEs (5)(6)(7)(8)(9)(10). Potential long-term problems include not only those seen after any abdominal procedure, such as ventral hernia, but also those specific to WLS procedures, e.g., gastric outlet obstruction, marginal ulceration, bowel obstruction, protein malnutrition, and vitamin deficiencies (3).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular concern are venous thromboembolism (66,(68)(69)(70) and sepsis. The latter occurs especially as a result of infection of the gastric band, anastomotic leak, and wound infection (52,(70)(71)(72).…”
Section: Postoperative Complications and Difficultiesmentioning
confidence: 99%
“…Leaks are difficult to diagnose, a heart rate above 120 beats/min and respiratory distress/failure are the most common manifestations of anastomotic leak (68,70,85). It should be noted that anastomotic leaks after bariatric surgery frequently become clinically apparent after discharge (86).…”
Section: Postoperative Complications and Difficultiesmentioning
confidence: 99%
“…9,10 A multivariate logistic regression analysis in a study that included more than 3000 patients who underwent LRYGB concluded that ASL was one of the strongest independent risk factors for postoperative death. 11 Fortunately, the incidence of ASL is relatively low at 0.4%-5.2%. [11][12][13][14][15] It is pertinent, however, to mention that experience performing LRYGB plays an important role in lowering the ASL rate, with large retrospective series revealing an almost 40% reduction in ASL as the surgeons became more adept using the technique.…”
Section: Anastomotic or Staple Line Leaksmentioning
confidence: 99%